Holy City Building Blocks (The Biblical archaeology review, 2025)
In the area of Har Hotzvim in northwestern Jerusalem, excavators with the Israel Antiquities Authority are exposing the secrets of an immense stone quarry that likely supplied the primary building material for major projects in Jerusalem during the Second Temple period. Although only about an acre of the quarry has been revealed so far, it […]